Organização de lideranças no bairro da Vilinha, Imperatriz-MA, uma área de ocupação - COSTA, Raimundo Nonato Barbosa (Universidade Federal do Pará, 2011)
This work has as objective to present an analysis on the urban problem in an occupation area in the neighborhood of the Villa, municipal district of Empress, highlighting the organization forms and performance of leaderships with relationship to the conquests and improvements of the population, tends as base an analysis of the associative in the Vila and its invigoration in Brazil after the 1980. As theoretical foundation was approached the classic in the investigation of the phenomenon of the cities and urbanization process, like Weber, Castells, Rodrigues, Acevedo, Simonian and others. During the research, mobilizations were identified in the neighborhood towards better life conditions as the politics of health, education and safety, showing the impasses at the same time among the inhabitants and between these and the public power, in the conquest of improvements for the neighborhood. Another aspect that stands out in this analysis is the relationships of the popular movement in the Villa with the municipal public power and until Federal, standing out the negotiations with INFRAERO for the liberation of the area for the definitive territorial formation of the neighborhood and at the same time the presence of the woman's performance as pioneer leaderships in the organization of representative movements of the neighborhood. It is concluded finally that the popular movement developed an important work, but a lot of times gone back to the attendance, mainly developed by the performance of the Churches so that they didn't contribute to help in the conscience citizen's formation, what could be explained the reason of so much difficulties, that the neighborhood today mainly, as the infrastructure basic.